2017
DOI: 10.3390/ijms18050964
|View full text |Cite
|
Sign up to set email alerts
|

Nimodipine but Not Nifedipine Promotes Expression of Fatty Acid 2-Hydroxylase in a Surgical Stress Model Based on Neuro2a Cells

Abstract: Nimodipine is well characterized for the management of aneurysmal subarachnoid hemorrhage and has been shown to promote a better outcome and less delayed ischemic neurological deficits. Animal and clinical trials show neuroprotective efficacy following nerve injuries. We showed a neuroprotective effect on Neuro2a cells. Subsequent microarray analysis revealed—among others—fatty acid 2-hydroxylase (FA2H) upregulated by nimodipine in vitro, which is a component of myelin synthesis. Differentiated Neuro2a cells w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
1
7
1
Order By: Relevance
“…In previous studies, nimodipine concentrations between 1–20 µM were appropriate for achieving a neuroprotective effect in cell culture [11,12], which also applies to the present results. This suggests that the neuroprotective effects of nimodipine are not dose-dependent in the concentrations between 1–20 µM, but that the time of treatment seems to be critical.…”
Section: Discussionsupporting
confidence: 83%
See 4 more Smart Citations
“…In previous studies, nimodipine concentrations between 1–20 µM were appropriate for achieving a neuroprotective effect in cell culture [11,12], which also applies to the present results. This suggests that the neuroprotective effects of nimodipine are not dose-dependent in the concentrations between 1–20 µM, but that the time of treatment seems to be critical.…”
Section: Discussionsupporting
confidence: 83%
“…Our data have shown that there is a neuroprotective effect as a result of a 24-h pretreatment with nimodipine. The stress models were established in previous studies [11,12,26]. Ethanol treatment is able to induce oxidative stress through acetaldehyde metabolism, which inhibits mitochondrial respiration at the level of complex I (NADH-ubiquinone oxido-reductase) and the coupling site I of oxidative phosphorylation [27].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations